(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2023)
Along with the discourse of religious moderation echoed by the Ministry of Religious Affairs of the Republic of Indonesia, various digital platforms have played a role in disseminating the idea to the public. TikTok is one of the fastest-growing social apps that still occupies the top position on knowledge consumption or responding to a current issue. Currently, TikTok’engagement rate is higher than other apps are, in terms of consistency in content dissemination regarding religious moderation. This research aims to map the extent of the proliferation of ideas that still exist and the narrative contestation in addressing the issue of religious moderation on TikTok. This study is qualitative research by applying virtual ethnography method. For collecting the data, the research undertaken an observation and documentation of TikTok’s top and recent contents. Based on the stages of analysis, the contestation of the narrative of religious moderation is still happening dynamically and will potentially continue to recur. By utilizing the hashtags #moderationberagama and #tolakmoderasiberagama, they have a platform to attract a wider audience. #moderationberagama users are not only supporters of the moderation idea but also those who oppose it. Thus, every other viewer has the chance to read some inappropriate ideas. So it is necessary to internalize digital literacy proficient knowledge to the larger communities. Those who can turn the wheels of public attention towards a more precise understanding are everyone who can elaborate the knowledge in a persuasive and accessible way for all people, not just individuals with thousands of followers.